christian1904 wrote:
Hi Bunuel, hi other members,
first of all thanks a lot everybody who is and has been posting and answering questions here which is a great support to my preparation. I learned a lot from you guys.
Question on this one, I got answer D (4) and am not sure why exactly I'm wrong - could somebody comment? I calculated like this:
(-2)^2m = 2^9-m
<=> 4^m = 4^8-m
<=> m = 8-m
<=> m = 4
Thanks!
You made one small mistake \(2^{9-m} \ne 4^{8-m}\).
\(2^{9-m} = \frac{2^9}{2^m} = \frac{2^{2 * 4.5}}{2^m} = \frac{4^{4.5}}{2^m}\)
So, what you could have done was \(4^m = \frac{4^{4.5}}{2^m}\)
=> \(2^m = \frac{4^{4.5}}{4^m}\)
=> \(2^m = 4^{4.5 - m}\)
=> \(2^m = 2^{2*(4.5 - m)}\)
=> \(m = 2*(4.5 - m)\)
=> \(m = 9 - 2m\)
=> \(m = 3\)
But Bunuel's way was much faster.
Hope that helps.
_________________
The buttons on the left are the buttons you are looking for